The Effect of Spiritual Health on The Resilience of Level II Cadets at Maritime Higher Education in Jakarta - Nafaz, Trisya Nabila; Hasan, Aliah B. Purwakania; Rahmawati, Siti (International Conference on Sustainable Health Promotion, 2023)
Cadets have a different education system for general students. Cadets are required to enter the dormitory during the education period and follow all existing rules and schedules, sometimes the rules and schedules that exist make cadets feel unfree and feel pressured. Resilience is an individual's ability to survive difficult situations, and adapt and rise from those situations. One of the factors that influence resilience is spiritual health. Spiritual health is the condition of the individual's soul that is free from spiritual illness and the ability of the individual to develop potential. This study aims to determine the effect of spiritual health on resilience in level II cadets at XYZ Maritime Higher Education. This study used quantitative methods with simple regression analysis techniques. The sampling of this study used convenience sampling techniques as many as 105 cadets. The results showed that there was an effect of spiritual health of 26.1% on resilience and 73.9% influenced by other factors. The significance value with the t value is calculated > t table (6.030 > 1.659). Suggestions from this study can be developed with further analysis and using different variables and for The school institutions can enhance existing religious activities in schools to help cadets improve their spirituality.